Synergistic antimicrobial activity of lynronne-1 and EDTA against bovine mastitis pathogens - Moreira, Ana Julia S.; De Araújo Domingues, Katialaine C.; Camargo, Karine D.V. [UNESP]; Aulik, Nicole A.; Oyama, Linda B.; Huws, Sharon A.; Mantovani, Hilario C. (Oxford University Press (OUP), 2025)
Background: Bovine mastitis is the costliest disease in the dairy sector and the main cause of antibiotic use in dairy cattle, potentially contributing to the antimicrobial resistance crisis. Antimicrobial peptides (AMPs) offer promise as antibiotic alternatives for controlling mastitis pathogens. Methods: The efficacy of five AMPs (Lynronne-1 [Lyn-1], Lynronne-2 [Lyn-2], Bovicin HC5, AMP 660, and AMP 1043) and two bioactive compounds (disodium ethylenediaminetetraacetic acid [EDTA] and glycerol monolaurate) was assessed against a range of 35 mastitis-causing pathogens. The fractional inhibitory concentrations index (FICI) was calculated to determine the interaction effect and values ≤0.5 were indicative of synergism. Time-dependent killing assays were performed to assess bactericidal efficacy of the combination. Cytotoxicity was evaluated using the MTT assay and haemolytic activity was assessed against fresh bovine erythrocytes. Results: Lyn-1 and EDTA exhibited the highest broad spectrum antimicrobial activity and reduced bacterial growth (OD600...nm) by 95.1% and 86.9%, respectively. FICI values ranged from 0.1 to 0.5, indicating synergism. The combination of lyn-1 (0.03...mg/mL) and EDTA (1.02...mg/mL) exhibited higher antimicrobial activity against all bacterial strains, at significantly lower concentrations than each compound individually. Lyn-1-EDTA combination reduced viable population by >10 000-fold within 12...h. The combination was non-haemolytic in concentrations up to 8-fold the established MIC values (PŠ>Š0.05), although cytotoxic effects were observed at concentrations above MIC (PŠ<Š0.01). Conclusions: These findings highlight the therapeutic potential of Lyn-1 and Lyn-1-EDTA for developing antibiotic-free formulations to combat contagious and environmental mastitis pathogens and treat udder infections.